Birth of offspring from spermatid or somatic cell by co-injection of PLCζ-cRNA. Issue 2 (August 2020) - Hirose, Naoki; Wakayama, Sayaka; Inoue, Rei; Ito, Junya; Ooga, Masatoshi; Wakayama, Teruhiko
Abstract : Artificial oocyte activation is important for assisted reproductive technologies, such as fertilization with round spermatids (ROSI) or the production of cloned offspring by somatic cell nuclear transfer (SCNT). Recently, phospholipase Cζ (PLCζ)-cRNA was used to mimic the natural process of fertilization, but this method required the serial injection of PLCζ-cRNA and was found to cause damage to the manipulated oocytes. Here we tried to generate offspring derived from oocytes that were fertilized using round spermatid or somatic cell nuclear transfer with the co-injection of PLCζ-cRNA. After co-injecting round spermatids and 20 ng/µL of PLCζ-cRNA into the oocytes, most of them became activated, but the activation process was delayed by more than 1 h. With the co-injection method, the rate of blastocyst formation in ROSI embryos was higher (64%) compared with that of the serial injection method (55%). On another note, when SCNT was performed using the co-injection method, the cloned offspring were obtained with a higher success rate compared with the serial-injection method. However, in either ROSI or SCNT embryos, the birth rate of offspring via the co-injection method was similar to the Sr activation method. The epigenetic status of ROSI and SCNT zygotes that was examined showed no significant difference among all activation methods. The results indicated that although the PLCζ-cRNA co-injection method did not improve the production rate of offspring, this method simplified oocyte activation with less damage, and with accurate activation time in individual oocytes, it can be useful for the basic study of oocyte activation and development.